P114 The effect of light interventions on sleep macro- and micro-architecture in sleep and circadian rhythm disorders: A scoping review. (7th October 2021) - Pun, T; Phillips, C; Marshall, N; Comas, M; Hoyos, C; D'Rozario, A; Bartlett, D; Davis, W; Hu, W; Naismith, S; Cain, S; Postnova, S; et al.
Abstract: Introduction: Light interventions have been used to treat sleep and circadian rhythm disorders. However, there are limited studies on the effect of light on electroencephalographic (EEG) activity during sleep. Therefore, we aimed to provide an overview of research using light intervention on sleep macro- and micro-architecture. Methods: We searched for randomised controlled trials that used light interventions and examined the effect on sleep measured using EEG in MEDLINE, PubMed, CINAHL, CENTRAL and PsycINFO databases. We included studies that examined the light intervention on sleep EEG in participants with a sleep or circadian rhythm disorder. Results: Four studies met the inclusion criteria in patients with insomnia only. These studies reported only sleep macro-architecture outcomes with three studies showing no effect of the timing or intensity of light intervention on total sleep time, wake after sleep onset, sleep efficiency and sleep stage duration. Only one study reported a significantly higher sleep efficiency after night-time light intervention (>4, 000 lx, 21:00-23:00 h) compared with afternoon light intervention (>4, 000 lx, 15:00-17:00 h). However, none of these studies reported sleep micro-architecture (power spectral analysis). Conclusion: Overall, there was limited evidence about the effect of light intervention on EEG sleep measures and studies were confined to insomnia patients only. This review could not find any data on sleep EEG spectral power related to light interventions. Research needs to be conducted into the effect of lighting interventions in clinical populations on sleep macro- and micro-architecture to better understand the effect on objective sleep timing and quality.